PENGARUH KETERSEDIAAN OKSIGEN TERHADAP PERTUMBUHAN KAPANG RHIZOPUS SP. PADA PROSES FERMENTASI TEMPE SEBAGAI PENERAPAN BIOTEKNOLOGI TRADISIONAL - Anjani; Rismatul Fadillah; Intan Mara Claudia; Muhammad Ridho Ramadhani Santori; Sumardi; Berti Yolida; Nadya Meriza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Tempe is a traditional Indonesian food product obtained through a fermentation process that utilizes the activity of molds from the genus Rhizopus sp. on soybeans. Oxygen availability plays a crucial role in tempe fermentation, as Rhizopus sp. is an obligate aerobic mold that requires oxygen for optimal growth. This study was conducted to examine the extent to which oxygen availability affects the growth of Rhizopus sp. during the tempe fermentation process, while also serving as a practical application of traditional biotechnology in daily life. The study employed an experimental design with three different packaging treatments: banana leaves, perforated plastic, and non-perforated plastic. Fermentation took place over 48 hours at a temperature of 30–32°C. Observations of mycelium growth were conducted every 12 hours, focusing on several indicators: color, hyphal density, and the surface area covered by mycelium. These observations were supplemented by an assessment of tempeh’s physical quality, encompassing color, aroma, texture, and firmness. Based on the research results, it was found that the use of banana leaf packaging produced the densest, most even, and purest white mycelium growth, while also yielding tempeh with the highest physical quality and nutritional content compared to other types of packaging. Perforated plastic packaging yielded fairly good results, whereas non-perforated plastic packaging produced tempeh of the lowest quality due to restricted air circulation. It can be concluded that oxygen availability has a significant effect on the growth of Rhizopus sp. and the quality of the resulting tempeh. The better the air circulation within the packaging, the more optimal the fermentation process and the quality of the resulting tempe.